The Miners and the Mounties: The Royal North West Mounted Plice and the 1906 Lethbridge Strike - Baker, William (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1991)
Abstract This essay explores the nature of the relationship between police and workers using the 1906 strike of Lethbridge coalminers as a case study. Following a discussion of relevant literature and theoretical frameworks it examines in detail the relationship between the Lethbridge strikers and the Mounted Police. This interaction was extremely complex with each party having an influence on the other. Consequently, no definitive conclusion can be drawn as to the interpretative debate between pluralist theory and class coilflict theory insofar as police-striker relations are concerned.